2020
DOI: 10.1186/s12877-020-01889-x
|View full text |Cite
|
Sign up to set email alerts
|

Mental wellbeing in the German old age population largely unaltered during COVID-19 lockdown: results of a representative survey

Abstract: Background Older individuals are at increased risk of a severe and lethal course of COVID-19. They have typically been advised to practice particularly restrictive social distancing (‘cocooning’), which has sparked much debate on the consequences for their mental wellbeing. We aimed to provide evidence by conducting a representative survey among the German old population during COVID-19 lockdown. Methods A computer-assisted standardized telephone interview was conducted in a randomly selected and representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
110
0
16

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(156 citation statements)
references
References 32 publications
(19 reference statements)
20
110
0
16
Order By: Relevance
“…Finally, similar to the results by Röhr et al [24], our results did not support the common ageist stereotypes of 'the weak and vulnerable elderly' during the pandemic. These results have confirmed that older adults have social and psychological resources that allow them to face adversity.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Finally, similar to the results by Röhr et al [24], our results did not support the common ageist stereotypes of 'the weak and vulnerable elderly' during the pandemic. These results have confirmed that older adults have social and psychological resources that allow them to face adversity.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, most studies monitoring mental health indicators during the pandemic have been conducted with the younger population and have used online surveys [19][20][21]. Although some research has included older populations, the majority have been cross-sectional or longitudinal studies that began during the pandemic [7,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In relation to compliance, a minority of participants indicated that their lives had not changed at all because of the pandemic—most reported that they had adjusted to the pandemic and the cocooning guidelines. This finding is compatible with previous reports that older adults are relatively protected from the negative mental health effects of the pandemic [ 15 , 16 ], a finding which may be explainable with recourse to models such as the “strength and vulnerability integration” (SAVI) approach [ 23 ], or the selective optimization with compensation model of preserved wellbeing in later life [ 24 ]. According to these approaches, older adults strategise to maximise positive affect in later life, and minimize the experience of negative affect.…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that older adults had a lower threshold of social interaction prior to the pandemic, meaning that the restrictions brought about less disruption in this group than in the younger generation, whose social interactions were more severely curtailed. Similar patterns of preserved wellbeing for older people were found for the outcomes of psychological distress, negative affect, depression, and anxiety, in German and U.S. populations [ 15 , 16 ].…”
Section: Introductionsupporting
confidence: 59%
“…Umfassendere wissenschaftliche Erkenntnisse zu den psychosozialen Folgen von Isolationsmaßnahmen für ältere Menschen in Altenund Seniorenheimen liegen bisher jedoch noch nicht hinreichend vor [4]. Eine aktuelle Studie zeigte zumindest im kurzfristigen Verlauf bei älteren Personen keine Verschlechterung des psychischen Befundes [14]. Hier ist auch zu berücksichtigen, dass für jüngere Familien prinzipiell ein größeres Netzwerk im Fokus steht, für das sie während der Krise, u.a.…”
Section: Psychosoziale Folgen Der Sars-cov-2-pandemieunclassified